2015
DOI: 10.2147/ceor.s85213
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the health care burden of prescription opioid abuse in five European countries

Abstract: BackgroundOpioid abuse, including abuse of prescription opioids (“RxOs”) and illicit substances like heroin, is a serious public health issue in Europe. Currently, there is limited data on the magnitude of RxO abuse in Europe, despite increasing public and scientific interest in the issue. The purpose of this study was to use the best-available data to derive comparable estimates of the health care burden of RxO abuse in France, Germany, Italy, Spain, and the United Kingdom (EU5).MethodsPublished data on the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 20 publications
(23 reference statements)
1
28
0
Order By: Relevance
“…Increases in deaths occurred in the context of decreased prevalence of PO use but increased rates of heavy use and disorder among users (Han et al, 2015). Issues related to prescription opioids are worldwide, affecting European countries, Australia, and Canada (Berecki-Gisolf et al, 2017; Berterame et al, 2016; Degenhardt et al, 2013; Dhalla et al, 2011; European Monitoring Centre for Drugs and Addiction, 2014; Fischer et al, 2014; Shei et al, 2015; United Nations).…”
Section: Introductionmentioning
confidence: 99%
“…Increases in deaths occurred in the context of decreased prevalence of PO use but increased rates of heavy use and disorder among users (Han et al, 2015). Issues related to prescription opioids are worldwide, affecting European countries, Australia, and Canada (Berecki-Gisolf et al, 2017; Berterame et al, 2016; Degenhardt et al, 2013; Dhalla et al, 2011; European Monitoring Centre for Drugs and Addiction, 2014; Fischer et al, 2014; Shei et al, 2015; United Nations).…”
Section: Introductionmentioning
confidence: 99%
“…A 2012 review identified opioid analgesics as one of the most commonly misused medicines in Europe, although the authors also noted the limited available data [9]. A more recent study estimated the prevalence of prescription opioid abuse as 13.7 per 10,000 individuals for France, 11.0 per 10,000 for Germany, and 10.7 per 10,000 for the United Kingdom (UK), but less than 1 per 10,000 individuals for Spain and Italy [33]. Similar statistics are unavailable for Australia, but a substantial increase in opioid analgesic prescriptions and opioid-related hospitalisations and deaths has occurred over the past decade, suggesting increasing levels of misuse and abuse [8].…”
Section: Introductionmentioning
confidence: 99%
“…Prescription opioid overdose and illicit drug use or dependence were both associated with child injury. This suggests that community-level prescription opioid overdose is independently associated with community-level outcomes for children during this time period and should be considered in further studies in other parts of the United States [where prescription opioid rates can be approximately twice as high as California’s (Paulozzi et al, 2015)] and other high-income countries where non-medical prescription opioid use is less predominant but remains a public health concern (Shei et al, 2015). …”
Section: Discussionmentioning
confidence: 99%
“…Since the 1990s, medical use of prescription opioids has tripled with the predominant increase occurring in high income counties (International Narcotics Control Board, 2012). There is some evidence of emerging trends for medical and non-medical prescription opioid use within the European Union; however, the highest rates of increase have been observed within the United States (European Monitoring Centre for Drugs and Drug Addiction, 2011; International Narcotics Control Board, 2012; Shei et al, 2015). Between 1996 and 2011 in the United States, medical use of prescription opioids rose 1,448% while non-medical use (i.e., use without a prescription or in ways other than which it was prescribed) rose 4,680% (Atluri et al, 2014).…”
Section: Introductionmentioning
confidence: 99%